Microsoft SQL Server 2005 reporting services - Lisin, Michael (Sams Pub., 2006)
SQL Server Reporting enables the creation, management, and delivery of both traditional, paper-oriented reports and interactive, Web-based reports. An integrated part of the Microsoft business intelligence framework, Reporting Services combines the data management capabilities of SQL Server and Microsoft Windows Server with familiar and powerful Microsoft Office System applications to deliver real-time information to support daily operations and drive decisions. Microsoft SQL Server 2005 Reporting Services will help you understand Reporting Services from various perspectives: How it fits business scenarios How to install and configure Reporting Services Reporting Services components Developing reports As you progress to advanced user status, you will enjoy the chapter about accessing Reporting Services programmatically and extending Reporting Services, and you will be able to use this book as a convenient reference.